Mobile marketing future trends - CĂTOIU, Iacob; GÂRDAN, Daniel Adrian; GÂRDAN, Doru Lucian (Annals of Spiru Haret University. Economic Series, 2010)
The present article proposes an introspection into the field of a new marketing specialization – mobile marketing. The concept mainly refers to all marketing activities related to the new communication channel – Short Message Service, Multimedia Messaging Service, and internet access from mobile phone. The article provides, at the same time, a marketing perspective about future trends of mobile marketing and mobile media, and also a technical perspective related to the future mobile communication technologies in the field – the LTE (Long Term Evolution) – cellular communication system optimized to support packet-switched data services to enable mobile broadband. The conclusions of the article focus on the relevance of mobile marketing, techniques efficiency related to brand promotion, changing consumers attitude and the development of such techniques imposed by the new mobile communication system.